Student perceptions of low-tech active learning and mastery of introductory biomechanics concepts - Knudson, Duane; Wallace, Brian (Sports biomechanics, 2021)
This study documented student perceptions of five low-tech active learning exercises, their epistemology of learning, and examined the association between these variables and mastery of biomechanics concepts. Students (N = 152) in four introductory biomechanics courses at two universities completed the Biomechanics Concept Inventory (BCI) at the beginning and the end of the course. An additional 10-question survey was used at the end of the course to determine student perceptions of the active learning exercises and their epistemology of learning. Student learning of biomechanical concepts improved over levels reported in previous studies of traditional lecture instruction, but not as much as seen in other studies of active learning pedagogy in biomechanics and physics. Student perceptions of active learning were positive, particularly in individual rather than group exercises. A minority (12-16%) of these students had negative perceptions of group-based active learning exercises. Student perception of epistemology of learning was primarily constructivist; however, there was no evidence of these perceptions had associations with learning biomechanical concepts. Biomechanics instructors planning to use low-tech active learning exercises should communicate their philosophy of learning, expectations for the course, and progressively implement individual-based and group-based active learning experiences early in the course.